Protective Effects of a Red Orange and Lemon Extract (RLE) on the Hepatotoxicity Induced by Ochratoxin A in Rats - Consiglia Longobardi; Sara Damiano; Emanuela Vaccaro; Gabriele Ballistreri; Brunella Restucci; Orlando Paciello; Salvatore Florio; Roberto Ciarcia (MDPI AG, 2024)
Ochratoxin A (OTA) is a highly potent mycotoxin that contaminates many kinds of food and feed sources. Its significant impact on human health and animal productivity makes it a topic of particular concern. The role of specific bioactive compounds used as dietary antioxidants is believed to be substantial due to their capacity to act as free radical scavengers. Because of the well-known oxidative stress induced by OTA, the primary objective of this work was to evaluate the antioxidant effects of a standardized powder extract recovered from citrus processing waste, red orange and lemon extract (RLE), on liver damage induced by OTA in a rat model. This study aimed to examine the impact of oral administration of RLE (90 mg/kg b.w.) on hepatic function and oxidative balance in Sprague-Dawley rats (n = 6/group) treated with OTA (0.5 mg/kg b.w.) over a period of 14 days. The administration of OTA alone resulted in both biochemical changes and an imbalance in redox status in the liver. However, the use of RLE alleviated the activity of antioxidant enzymes and dramatically decreased the serum levels of ALT (alanine aminotransferase), AST (aspartate aminotransferase), and ALP (alkaline phosphatase), providing evidence of its protective benefits. Based on the findings from liver histology tests, the administration of RLE resulted in mitigation of lymphoplasmacytic inflammation, steatosis, and necrosis in the OTA group. These results indicate that the novel phytoextract RLE holds potential for application in the field of nutraceuticals.